Investigating the temporal trends of diabetes disease burden in China during 1990-2019 from a global perspective - Liu, Jinli; Shen, Mingwang; Zhuang, Guihua; Zhang, Lei (Frontiers in Endocrinology, 2024)
Introduction: Diabetes poses a global public health challenge and our understanding of its temporal evolution in China relative to the rest of the world is limited. Our study aims to comprehensively examine the temporal trend of diabetes burden in China from a global perspective.We analyzed data on diabetes incidence, prevalence, and mortality for individuals aged ≥20 years in China and globally from the Global Burden of Disease (GBD) 2019 study. We assessed trends in age-standardized incidence rate (ASIR) and age-standardized mortality rate (ASMR) of diabetes in China and globally by estimating annual percentage changes (EAPCs). We employed decomposition analysis to reveal factors driving the trend of diabetes burden in China.Results: During 1990-2019, the number of diabetes patients increased by 160% from 35.14 million to 91.70 million in China. The ASIR of diabetes increased from 249/100,000 person-years (pys) to 329/100,000 pys in China, which was lower than the global rate (419/100,000 pys in 2019). The EAPC of diabetes incidence was also lower in China compared to the global rate (1.02% vs. 1.57%). Consistently, the age-standardized prevalence rate of diabetes increased from 4788/100,000 pys to 8170/100,000 pys during 1990-2019 in China, which remained lower than the corresponding global rate (8827/100,000 pys in 2019). Further, the ASMR of diabetes increased from 9/100,000 pys to 15/100,000 pys during 1990-2019 in China, which was lower than the corresponding global rate (30/100,000 pys in 2019). However, EAPC of diabetes mortality in China was much higher than the global level (1.75% vs. 1.07%). Globally, the rising diabetes burden was predominantly attributed to population growth (55.2%) and epidemiologic changes (24.6%). In comparison, population growth (48.9%) also played an important role in the increasing diabetes burden in China, but aging (43.7%) was second major contributor.Our findings show that diabetes burden in China followed a global increasing trend during 1990-2019. Notably, aging has a very substantial contribution to the increase in diabetes burden in China in addition to population growth.